Properties, Pharmacology, and Pharmacokinetics of Active Indole and Oxindole Alkaloids in Uncaria Hook - Kushida, Hirotaka; Matsumoto, Takashi; Ikarashi, Yasushi (Frontiers in Pharmacology, 2021)
Uncaria Hook (UH) is a dry stem with hook of Ucaria plant and is contained in Traditional Japanese and Chinese medicine such as yokukansan, yokukansankachimpihange, chotosan, Gouteng-Baitouweng, and Tianma-Gouteng Yin. UH contains active indole and oxindole alkaloids and has the therapeutic effects on ailments of the cardiovascular and central nervous systems. The recent advances of analytical technology led to reports of detailed pharmacokinetics of UH alkaloids. These observations of pharmacokinetics are extremely important for understanding the treatment’s pharmacological activity, efficacy, and safety. This review describes properties, pharmacology, and the recently accumulated pharmacokinetic findings of UH alkaloids, and discusses challenges and future prospects. UH contains major indole and oxindole alkaloids such as corynoxeine, isocorynoxeine, rhynchophylline, isorhynchophylline, hirsuteine, hirsutine, and geissoschizine methyl ether (GM). These alkaloids exert neuroprotective effects against Alzheimer’s disease, Parkinson’s disease, and depression, and the mechanisms of these effects include anti-oxidant, anti-inflammatory, and neuromodulatory activities. Among the UH alkaloids, GM exhibits comparatively potent pharmacological activity (e.g., agonist activity at 5-HT1A receptors). UH alkaloids are absorbed into the blood circulation and rapidly eliminated when orally administered. UH alkaloids are predominantly metabolized by Cytochrome P450 (CYP) and converted into various metabolites, including oxidized and demethylated forms. Regarding GM metabolism by CYPs, a gender-dependent difference is observed in rats but not in humans. Several alkaloids are detected in the brain after passing through the blood–brain barrier in rats upon orally administered. GM is uniformly distributed in the brain and binds to various channels and receptors such as the 5-HT receptor. By reviewing the pharmacokinetics of UH alkaloids, challenges were found, such as differences in pharmacokinetics between pure drug and crude drug products administration, food-influenced absorption, metabolite excretion profile, and intestinal tissue metabolism of UH alkaloids. This review will provide readers with a better understanding of the pharmacokinetics of UH alkaloids and their future challenges, and will be helpful for further research on UH alkaloids and crude drug products containing UH.